Electrolyte additive, electrolyte, battery and electric equipment

By using the first additive with a benzene ring structure and the second additive with a ring structure in the electrolyte of a lithium-ion battery, the problems of high interface impedance and poor stability of the SEI film caused by the electrolyte additive are solved, and the battery performance is achieved Improvements, including improvements in power performance, rate performance and cycle performance.

CN119447455APending Publication Date: 2025-02-14BYD CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411220378.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The electrolyte additives of existing lithium-ion batteries have problems such as high interface impedance and poor stability of SEI films, which affect the performance of the battery.

Method used

Using an electrolyte additive, including a compound with a benzene ring structure in the first additive and a sulfur compound with a ring structure in the second additive, the film forming properties of the SEI film are regulated, and the interface impedance is reduced, and the power and rate performance of the battery are improved. and cycle performance.

Benefits of technology

It effectively improves the stability of the SEI film, reduces the interface impedance, improves the power, rate and cycle performance of the battery, and enhances the fast charging capability and service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447455A_ABST
    Figure CN119447455A_ABST
Patent Text Reader

Abstract

The invention discloses an electrolyte additive, an electrolyte, a battery and electric equipment. The electrolyte additive comprises a first additive and a second additive, the first additive has a structure as shown in a formula (I); # imgabs0 # formula (I); r < 1 >, R < 2 >, R < 3 >, R < 4 > and R < 5 > are respectively and independently selected from hydrogen, hydroxyl, alkyl of C1 to C10 or alkoxy of C1 to C10; the second additive comprises a compound with a cyclic structure, and the cyclic structure contains sulfur atoms. The electrolyte additive can effectively regulate and control the film-forming property of an SEI film, improve the stability of the SEI film, reduce the interface impedance and improve the power performance, the rate capability and the cycle performance of a battery, and is high in fast charging capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to electrolyte additives, electrolytes, batteries and electrical equipment. Background Art

[0002] Lithium-ion batteries have been developing rapidly since the 1990s. They have the characteristics of high voltage, high specific energy, long charge and discharge life, safety and environmental protection, and have been widely used in mobile devices, electric vehicles and other fields. The electrolyte is an important component of lithium-ion batteries. It can transfer lithium ions from the negative electrode to the positive electrode and form a dense solid electrolyte interface (SEI) film on the surface of the negative electrode, thereby preventing the embedding of electrolyte anions and the continuous loss of active materials.

[0003] For lithium-ion batteries, the electrolyte is mainly composed of solvents, lithium salts and electrolyte additives. Currently available electrolyte additives have defects such as high SEI membrane interface impedance and poor stability, which affect the performance of lithium-ion batteries. Summary of the invention

[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to provide an electrolyte additive, an electrolyte, a battery and an electrical device. The electrolyte additive of the present application can effectively regulate the film-forming property of the SEI film, improve the stability of the SEI film, reduce the interface impedance, improve the power performance, rate performance and cycle performance of the battery, and has a strong fast charging capability.

[0005] In a first aspect, the present application provides an electrolyte additive. The electrolyte additive includes a first additive and a second additive;

[0006] The first additive has a structure shown in formula (I);

[0007]

[0008] R1, R2, R3, R4 and R5 are each independently selected from hydrogen, hydroxyl, C1-C 10 Alkyl or C1~C 10 Alkoxyl groups;

[0009] The second additive includes a compound having a ring structure, and the ring structure contains a sulfur atom.

[0010] The electrolyte additive of the present invention has a good steric hindrance effect in the electrolyte because the first additive has a benzene ring structure, which helps to reduce the interface impedance, thereby optimizing the transmission efficiency of ions and improving the ion conductivity. In addition, this structure also helps to form a more stable and uniform SEI film to maintain the performance of the battery during long-term cycling. The second additive can enhance the cycle stability of the battery in a high temperature environment and improve the battery life. The first additive and the second additive can play a synergistic effect, improve the power performance, rate performance and cycle performance of the battery, and have a strong fast charging capability.

[0011] According to some embodiments of the present application, the electrolyte additive may also have the following additional technical features:

[0012] According to some embodiments of the present application, R1, R2, R3, R4 and R5 are each independently selected from hydrogen, hydroxyl, tert-butyl, -(CH2) m CH3 or -O(CH2) n CH3;

[0013] m is an integer selected from 0 to 3;

[0014] n is an integer selected from 0-3.

[0015] According to some embodiments of the present application, at least one group among R1, R2 and R5 is selected from tert-butyl.

[0016] According to some embodiments of the present application, R1, R2, R3, R4 and R5 do not contain tert-butyl groups and formula (I) is a symmetrical conjugated structure.

[0017] According to some embodiments of the present application, the R1 is selected from hydrogen, tert-butyl, methyl or ethyl;

[0018] Said R2 is selected from hydrogen, hydroxyl, tert-butyl, methyl or ethyl;

[0019] Said R3 and R4 are each independently selected from hydrogen, hydroxyl, methyl or ethyl;

[0020] The R5 is selected from methyl, ethyl, hydroxy, methoxy, ethoxy or tert-butyl.

[0021] According to some embodiments of the present application, the first additive includes At least one of .

[0022] According to some embodiments of the present application, the ring structure also contains oxygen atoms.

[0023] According to some embodiments of the present application, the compound having a cyclic structure includes at least one of methylene methanedisulfonate, propylene sulfite and vinyl sulfite.

[0024] According to some embodiments of the present application, the mass ratio of the first additive to the second additive is 1:(0.01-100), preferably 1:(1-20).

[0025] According to some embodiments of the present application, the electrolyte further includes: a third additive, and the third additive includes vinylene carbonate.

[0026] According to some embodiments of the present application, the mass ratio of the first additive to the third additive is (0.002-15):1, preferably (0.01-0.2):1.

[0027] The second aspect of the present application provides an electrolyte. The electrolyte includes the electrolyte additive described in the first aspect of the present application. The electrolyte of the present application can effectively regulate the film-forming property of the SEI film, improve the stability of the SEI film, reduce the interface impedance, and improve the power performance, rate performance and cycle performance of the battery.

[0028] According to some embodiments of the present application, based on the total mass of the electrolyte, the mass proportion of the first additive is 0.01% to 3%, preferably 0.05% to 1%.

[0029] According to some embodiments of the present application, based on the total mass of the electrolyte, the mass proportion of the second additive is 0.1% to 5%, preferably 0.5% to 1.5%.

[0030] According to some embodiments of the present application, based on the total mass of the electrolyte, the mass proportion of the third additive is 0.1% to 10%, preferably 4% to 6%.

[0031] The third aspect of the present application provides a battery. The battery includes the electrolyte described in the second aspect. The battery of the present application has good power performance, rate performance and cycle performance.

[0032] The fourth aspect of the present invention provides an electric device. The electric device comprises the battery of the third aspect. Therefore, the electric device of the present application has high-efficiency energy output and excellent service life and safety performance.

[0033] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0035] Figure 1The voltage-SOC distribution curve of a lithium-ion battery at 2.5C is shown. DETAILED DESCRIPTION

[0036] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.

[0037] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.

[0038] The endpoints and any values ​​of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this application.

[0039] In the present application, the terms "comprise" or "include" are open expressions, that is, including the contents specified in the present application but not excluding other contents.

[0040] At present, the conventional electrolyte system mainly includes lithium salts, solvents and additives. In this system, the solvent will coordinate with lithium ions before anions, and the SEI film finally formed has a high proportion of organic components. For example, the organic component lithium diethylene carbonate (LEDC) formed by ethylene carbonate (EC) is unstable and easily decomposes at high temperatures; poly (VC) formed by vinylene carbonate (VC) has high impedance characteristics; sulfur additives such as methylene methanedisulfonate (MMDS) will significantly increase the interface impedance, and the increase in battery interface impedance will reduce battery power, deteriorate rate performance, and increase battery heat generation and the risk of lithium precipitation during high-rate charge and discharge, which is not conducive to the improvement of battery cycle performance and power performance.

[0041] In the electrolyte of lithium-ion batteries, "solvation of lithium ions" refers to the electrostatic interaction between lithium ions and anions and solvents in the electrolyte, moving in the form of a "solvation sheath" to form a solvation structure. Different solvation structures have different molecular orbital energy levels, which affect the electrode-electrolyte interface, i.e., the SEI film. In the electrolyte system, compared with anions, the solvent has a stronger binding energy with lithium ions, and they will form solvation coordination with lithium ions before anions, resulting in the anions being "shielded" by the solvent, causing the solvent to be reduced to a film before the anions during formation. The anion-rich SEI film has a high inorganic salt content ratio. Inorganic salts such as LiF, Li2O, and Li2CO3 have electronic insulation and high ionic conductivity, which can improve the stability of the SEI film and have better electrochemical properties. In view of this, the present application adds a first additive and a second additive to the electrolyte. Since the first additive has a benzene ring structure, it has a good steric hindrance effect in the electrolyte, which helps to reduce the interface impedance, thereby optimizing the ion transmission efficiency and improving the ionic conductivity. Moreover, this structure also helps to form a more stable and uniform solid electrolyte interface (SEI) film to maintain the performance of the battery during long-term cycling. The second additive can enhance the cycle stability of the battery in a high temperature environment and improve the battery life. The first additive and the second additive can play a synergistic effect to improve the power performance, rate performance and cycle performance of the battery, and have strong fast charging capability.

[0042] To this end, the first aspect of the present application provides an electrolyte additive. According to an embodiment of the present application, the electrolyte additive includes a first additive and a second additive;

[0043] The first additive has a structure shown in formula (I);

[0044]

[0045] R1, R2, R3, R4 and R5 are each independently selected from hydrogen, hydroxyl, C1-C 10 Alkyl or C1~C 10 Alkoxyl groups;

[0046] The second additive includes a compound having a ring structure, and the ring structure contains a sulfur atom.

[0047] In the present application, the term "cyclic structure" refers to a closed ring formed by atoms connected by covalent bonds.

[0048] The first additive of the present application has a benzene ring structure and has high steric hindrance. At the same time, since the hydroxyl group is also a relatively large group, its oxygen atoms and hydrogen atoms are relatively large in volume relative to the carbon atoms on the benzene ring, so additional steric hindrance will be introduced on the benzene ring. Thus, in the coordination of the lithium ion solvation structure, the solvation structure can be adjusted to increase the ability of anions to participate in solvation coordination, regulate the film-forming properties of the SEI film, and form a uniform SEI film rich in LiF and Li2O. The SEI film has electronic insulation and high ionic conductivity, can improve the stability of the SEI film, has low interface impedance, helps to improve the transmission efficiency of ions, improves battery power and rate performance, and maintains the performance of the battery during long-term cycling.

[0049] In the present application, the term "film-forming property" refers to the film-forming process and characteristics, including, for example, film composition, film-forming rate, and film thickness.

[0050] The second additive of the present application has a ring structure, and the ring structure contains sulfur atoms, which can form sulfur-containing organic matter or salts during battery formation or circulation. The second additive with this structure will improve the composition of the SEI film and delay the exothermic decomposition of the SEI film under high temperature conditions, thereby enhancing the cycle stability of the battery under high temperature environment and ensuring that the battery can maintain good performance even at extreme temperatures. However, the second additive with this ring structure will increase the interface impedance. Since the first additive has the effect of reducing the interface impedance, the increase in interface impedance caused by the introduction of the second additive can be reduced.

[0051] In addition, during the battery formation process, the formation process of the SEI film is a reduction process of the solvent or additive, that is, the solvent or additive will open the ring to generate anion free radicals and undergo a polymerization reaction. Since the second additive has a ring structure, an opening reaction will occur during the battery formation process to form anion free radicals. These free radicals are highly active and easily undergo polymerization reactions with other molecules or free radicals to form an SEI film on the negative electrode. However, the second additive is prone to over-polymerization, which may cause the SEI film to be too thick and affect ion transport. It is also easy to polymerize in non-electrode areas, resulting in increased electrolyte viscosity or precipitation, which will also affect electron and ion transport, increase the internal resistance of the battery, and reduce battery performance.

[0052] Since the first additive has a benzene ring structure, it has excellent antioxidant properties. Under the influence of steric hindrance, the hydrogen atoms of the hydroxyl group on the benzene ring are easily removed to form free radicals, which capture free radical anions formed by chemical reactions or thermal reactions, terminate the generation of anion free radicals, play an inhibitory role, regulate the film-forming properties of the second additive, and promote it to form a good SEI film with appropriate thickness, which can avoid excessive polymerization of the second additive or polymerization in the non-negative electrode area.

[0053] The first additive can adjust the solvation structure, improve the stability of the SEI film and reduce the interface impedance, but it is easy to cause the cycle performance of the product to weaken. Since the second additive can improve the cycle stability of the enhanced battery in a high temperature environment, it can weaken the defect of weakened product cycle performance caused by adding a large amount of the first additive.

[0054] Therefore, the first additive and the second additive have a synergistic effect, which can not only improve the power density and charge and discharge rate performance of the battery, enabling the battery to quickly respond to high power demands and enhance fast charging capabilities, but also enhance the cycle stability of the battery and extend the service life of the battery.

[0055] According to some embodiments of the present application, R1, R2, R3, R4 and R5 are each independently selected from hydrogen, hydroxyl, tert-butyl, -(CH2) m CH3 or -O(CH2) n CH3;

[0056] m is an integer selected from 0 to 3, for example, 0, 1, 2 or 3;

[0057] n is an integer selected from 0 to 3, for example, 0, 1, 2 or 3.

[0058] Thus, the first additive having the above-mentioned groups further has a better steric hindrance effect, which helps to further reduce the interface impedance and form a more stable and uniform SEI film. Among them, the tert-butyl group is a group with a large steric hindrance, which shows a significant steric hindrance effect in the electrochemical reaction. It and the benzene ring jointly adjust the solvation structure, increase the anion's ability to participate in the solvation coordination, and form a uniform, stable and LiF and Li2O-rich SEI film. The SEI film has electronic insulation and high ionic conductivity, which can improve the stability of the SEI film, low interface impedance, and is conducive to the transmission efficiency of ions. It also has a strong antioxidant capacity, which helps to better regulate the reduction of the second additive into a film and improve the power performance, rate performance and cycle performance of the battery.

[0059] According to some embodiments of the present application, at least one of R1, R2 and R5 is selected from tert-butyl. Thus, the first additive having the above group further has a better steric hindrance effect, which helps to further reduce the interface impedance and form a more stable and uniform SEI film.

[0060] According to some embodiments of the present application, R1, R2, R3, R4 and R5 do not contain tert-butyl groups and formula (I) is a symmetrical conjugated structure. The presence of the conjugated structure and the hydroxyl group tends to increase the π-π stacking force or other non-covalent forces between molecules, which compete with the polymerization reaction, thereby inhibiting polymerization. In addition, the conjugated structure tends to reduce the acidity of the hydroxyl group, thereby reducing its reactivity with other reactants (such as free radicals or cationic initiators), inhibiting the initiation of the polymerization reaction.

[0061] In this application, the terms "conjugated structure" and "conjugated system" are used interchangeably, and refer to a structure in which the electron orbitals of adjacent atoms or groups overlap or interact, the electrons delocalize, the system energy decreases, and the bond lengths are averaged. "Symmetrical conjugated structure" refers to a structure in which both sides of the conjugated system in a molecule have identical or mirror-symmetrical arrangements of atoms or atomic groups.

[0062] According to some embodiments of the present application, R1 is selected from hydrogen, tert-butyl, methyl or ethyl;

[0063] R2 is selected from hydrogen, hydroxy, tert-butyl, methyl or ethyl;

[0064] R3 and R4 are each independently selected from hydrogen, hydroxy, methyl or ethyl;

[0065] R5 is selected from methyl, ethyl, hydroxy, methoxy, ethoxy or tert-butyl.

[0066] Therefore, the first additive having the above-mentioned group further has a better steric hindrance effect, which helps to further reduce the interfacial impedance, form a more stable and uniform SEI film, and can also better regulate the reduction film formation of the second additive, thereby improving the power performance, rate performance and cycle performance of the battery.

[0067] According to some embodiments of the present application, the first additive includes (2,6-di-tert-butyl-4-methylphenol, CAS No.: 128-37-0), (tert-butylcatechol, CAS No.: 98-29-3), (tert-Butyl-4-hydroxyanisole, CAS No.: 25013-16-5), (hydroquinone, CAS No.: 123-31-9), (p-Hydroxyanisole, CAS No.: 150-76-5). As a result, the first additive has a better steric hindrance effect, which helps to further reduce the interface impedance and form a more stable and uniform SEI film. It can also better regulate the reduction film formation of the second additive and improve the power performance, rate performance and cycle performance of the battery.

[0068] According to some embodiments of the present application, the ring structure further contains oxygen atoms. For example, the compound having a ring structure includes at least one of methylene methane disulfonate (MMDS), propylene sulfite (PS), and ethylene sulfite (ES). Thus, the composition of the SEI film can be better improved, and the exothermic decomposition of the SEI film under high temperature conditions can be delayed, thereby enhancing the cycle stability of the battery under high temperature environment, ensuring that the battery can maintain good performance even at extreme temperatures.

[0069] According to some embodiments of the present application, the mass ratio of the first additive to the second additive is 1:(0.01-100), for example, 1:0.01, 1:0.1, 1:1, 1:5, 1:10, 1:15, 1:20, 1:30, 1:50, 1:80, 1:100, etc., wherein 1:(1-20) is preferred. Thus, the first additive and the second additive are matched in the above ratio to better exert the synergistic effect, which can improve the stability of the SEI film, reduce the interface impedance, and help improve the ion transmission efficiency, and can also improve the cycle stability of the battery, and can better regulate the film-forming property of the second additive, and improve the power performance, rate performance and cycle performance of the battery.

[0070] According to some embodiments of the present application, the electrolyte additive further includes: a third additive, and the third additive includes vinylene carbonate.

[0071] Vinylene carbonate (VC) has a lower reduction potential and can be reduced to form a film at the negative electrode before the solvent. The resulting polymer protective film has good thermal stability, which can improve the high temperature stability of the SEI film and effectively improve the battery cycle life. However, it has poor conductivity and will increase the interface impedance. The increase in battery impedance will reduce battery power, deteriorate rate performance, and increase battery heat generation and the risk of lithium precipitation during high rate charge and discharge. In addition, VC also has a ring structure, which will open the ring during the battery formation process, undergo polymerization, and form a film on the negative electrode.

[0072] Since the first additive has excellent interfacial impedance reduction and antioxidant capabilities, it can effectively prevent the third additive from over-polymerizing or polymerizing in the non-negative electrode area. The first additive, the second additive and the third additive play a synergistic effect, which is conducive to the formation of a SEI film with better performance, thereby better improving the power performance, rate performance and cycle performance of the battery.

[0073] According to some embodiments of the present application, the mass ratio of the first additive to the third additive is (0.002-15):1, for example, 0.002:1, 0.01:1, 0.02:1, 0.05:1, 0.1:1, 0.2:1, 0.4:1, 0.5:1, 1:1, 1:2, 1:4, 1:5, 1:8, 1:10, 1:12, 1:15, etc., wherein (0.01-0.2):1 is preferred. Thus, the first additive and the third additive are matched in the above ratio, and can better exert a synergistic effect with the second additive, which can not only improve the stability of the SEI film, reduce the interface impedance, and help improve the ion transmission efficiency, but also improve the cycle stability of the battery, and can better regulate the film-forming property of the second additive, and improve the power performance, rate performance and cycle performance of the battery.

[0074] The second aspect of the present application provides an electrolyte. The electrolyte includes the electrolyte additive described in the first aspect. The electrolyte of the present application can effectively regulate the film-forming property of the SEI film, improve the stability of the SEI film, reduce the interface impedance, and improve the power performance, rate performance and cycle performance of the battery.

[0075] According to some embodiments of the present application, based on the total mass of the electrolyte, the mass proportion of the first additive is 0.01% to 3%, for example, 0.01%, 0.03%, 0.05%, 0.08%, 0.1%, 0.3%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, etc., wherein 0.05% to 1% is preferred. Thus, the mass proportion of the first additive meets the given conditions, can better adjust the solvation structure, increase the ability of anions to participate in solvation coordination, the film-forming property of the SEI film is better, and a uniform SEI film rich in LiF and Li2O can be formed, the stability of the SEI film is improved, the interface impedance is low, the ion transfer efficiency is high, and the antioxidant performance can be better exerted, the film-forming property of the second additive and the third additive is regulated, and the power performance, rate performance and cycle performance of the battery are improved. Moreover, it is not easy to cause crystal precipitation due to reaching the upper limit of solubility. In addition, since the first additive has a large steric hindrance group and low conductivity, it may increase the impedance of the electrolyte to a certain extent. Adding the first additive that meets the given conditions can reduce the impedance of the battery and facilitate ion and electron transmission. Furthermore, the first additive has good solubility in the electrolyte.

[0076] According to some embodiments of the present application, based on the total mass of the electrolyte, the mass proportion of the second additive is 0.1% to 5%, for example, 0.1%, 0.3%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc., preferably 0.5% to 1.5%. Thus, the mass proportion of the second additive meets the given conditions, which can better improve the cycle performance of the battery and extend the service life.

[0077] According to some embodiments of the present application, based on the total mass of the electrolyte, the mass proportion of the third additive is 0.1% to 10%, for example, 0.1%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., preferably 4% to 6%. Thus, the high temperature stability of the SEI film can be further improved, and the battery cycle life can be effectively improved.

[0078] According to some embodiments of the present application, the electrolyte further includes: an electrolyte salt and a solvent.

[0079] According to some embodiments of the present application, the solvent is a non-aqueous organic solvent, wherein the non-aqueous organic solvent is the main component of the electrolyte and should have a high solubility of lithium salts so that the electrolyte has a high ionic conductivity. Its specific type is not particularly limited, and those skilled in the art can select it according to actual needs. As some specific examples, the non-aqueous organic solvent includes at least one of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethylene carbonate (EC), fluoroethylene carbonate (FEC), propylene carbonate (PC), butylene carbonate (BC), diethyl sulfite (DES), γ-butyrolactone (BL), dimethyl sulfoxide (DMSO), ethyl acetate, and methyl acetate. Preferably, at least one of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC). The solvent in the electrolyte is an important carrier for ion transmission. When the electrolyte salt is dissolved, it can have a high electronic conductivity, and then the cycle life, charge and discharge rate, high and low temperature performance, and energy density of the battery can be improved by selecting the above solvent.

[0080] According to some embodiments of the present application, the electrolyte salt may include at least one of LiPF6, LiFSI, LiTFSI, LiTNFSI, LiFNFSI, LiBF4, LiBOB, LiClO4, LiAsF6, LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiCF3SO3, LiB(C2O4)2 or lithium tetrafluorooxalate phosphate. Thus, the electrolyte can be applied to lithium-ion batteries.

[0081] It should be noted that the features and advantages described above for the electrolyte additive are also applicable to the electrolyte and will not be repeated here.

[0082] The third aspect of the present application provides a battery. The battery includes the electrolyte described in the second aspect. The battery of the present application has good power performance, rate performance and cycle performance.

[0083] According to some embodiments of the present application, the battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays a role in conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0084] According to some embodiments of the present application, the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side surface of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material.

[0085] Exemplarily, when the positive electrode plate is used in a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.8 Co 0.15 Al 0.05 O2) or at least one of its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, or a composite material of lithium iron manganese phosphate and carbon.

[0086] According to some embodiments of the present application, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the polymer material base. For example, the composite negative electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and other substrates).

[0087] According to some embodiments of the present application, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0088] According to some embodiments of the present application, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0089] According to some embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet (such as positive electrode active material, conductive agent, binder) are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0090] According to some embodiments of the present application, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material.

[0091] According to some embodiments of the present application, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).

[0092] According to some embodiments of the present application, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: graphite, soft carbon, hard carbon, silicon-based material, tin-based material, etc. The silicon-based material may include at least one of elemental silicon, silicon oxide compound, silicon carbon compound, silicon nitrogen compound and silicon alloy. The tin-based material may include at least one of elemental tin, tin oxide compound and tin alloy.

[0093] According to some embodiments of the present application, the negative electrode active material layer may further optionally include a binder. The binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0094] According to some embodiments of the present application, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0095] According to some embodiments of the present application, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0096] According to some embodiments of the present application, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet (such as negative electrode active material, conductive agent, binder and any other components) are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0097] The present invention has no particular limitation on the type of the isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected. According to an embodiment of the present application, the isolation membrane may be made of at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride.

[0098] According to some embodiments of the present application, the battery may include an outer package for packaging a positive electrode sheet, a negative electrode sheet, and an electrolyte.

[0099] According to some embodiments of the present application, the outer packaging may include a shell and a cover plate. The shell may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell has an opening connected to the receiving cavity, and the cover plate can be covered on the opening to close the receiving cavity.

[0100] According to some embodiments of the present application, the outer packaging of the battery may be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell.

[0101] The outer packaging of the battery may also be a soft package, such as a bag-type soft package, and the material of the soft package may be an aluminum-plastic film or the like.

[0102] The battery of the present application may include a battery cell form, a battery module form and a battery pack form. The battery cell includes a shell, a pole core and an electrolyte. The shell is formed with a containing space. The pole core and the electrolyte are arranged in the containing space. The pole core may include a positive electrode, a negative electrode and a separator. The positive electrode, the negative electrode and the separator are arranged in a stacked or wound manner. In some embodiments, the battery cells can be assembled into a battery module. The number of battery cells contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module. In some embodiments, the battery module can also be assembled into a battery pack. The number of battery modules contained in the battery pack can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery pack.

[0103] The fourth aspect of the present invention provides an electric device. According to an embodiment of the present application, the electric device includes the battery of the third aspect. Therefore, the electric device of the present application has high-efficiency energy output and excellent service life and safety performance.

[0104] Battery cells, battery modules, and battery packs can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, energy storage systems, etc.

[0105] As an electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.

[0106] As an embodiment, the electric device may be a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for high power and high energy density of the battery, a battery pack or a battery module may be used.

[0107] As another embodiment, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.

[0108] It should be noted that the features and advantages described above for the electrolyte of the second aspect of the present application are also applicable to the battery of the third aspect and the electrical equipment of the fourth aspect of the present application, and will not be repeated here.

[0109] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0110] Example 1

[0111] 1. Preparation of positive electrode

[0112] The positive electrode active material LiFePO4, the conductive agent carbon black, and the binder PVDF are fully mixed in a mass ratio of 95:2.5:2.5, and the solvent NMP is added, and stirred under the action of a vacuum mixer until the slurry is evenly mixed to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the current collector aluminum foil, and after the electrode sheet is completely dried, it is rolled and die-cut to obtain a positive electrode sheet.

[0113] 2. Preparation of negative electrode sheet

[0114] The negative electrode active material graphite, the conductive agent carbon black, the binder SBR, and the thickener CMC are mixed in a mass ratio of 93:1:4:2, and deionized water is added as a solvent. The mixture is stirred under the action of a vacuum mixer until the slurry is uniformly mixed to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the current collector copper foil, and after the electrode sheet is completely dried, the positive electrode sheet is obtained by rolling and die-cutting.

[0115] 3. Preparation of electrolyte

[0116] In an argon glove box, ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain a mixed solvent. Lithium hexafluorophosphate (LiPF6), vinylene carbonate (VC), methylene disulfonate (MMDS), and 2,6-di-tert-butyl-4-methylphenol (BHT) are added to the above mixed solvent to obtain an electrolyte. Based on the total mass of the electrolyte, the mass proportion of lithium hexafluorophosphate is 12%, the mass proportion of vinylene carbonate is 5%, the mass proportion of methylene disulfonate is 1%, and the mass proportion of 2,6-di-tert-butyl-4-methylphenol is 1.5%.

[0117] 4. Isolation film

[0118] The diaphragm is a PE-coated ceramic diaphragm with a thickness of 12 μm.

[0119] 5. Lithium-ion battery preparation

[0120] The negative electrode sheet, separator, positive electrode sheet and separator are stacked in order, and the above order is repeated to fix them with high temperature resistant tape, and then the positive and negative electrode tabs are welded, and the battery cell is encapsulated with aluminum plastic film. The battery cell is vacuum dried at 80℃ for 72h, and then the corresponding prepared electrolyte is injected and encapsulated, and then the lithium-ion battery is obtained through the steps of standing, pressurized formation, aging, exhaust, and capacity division.

[0121] The difference between Examples 2 to 23 and Comparative Examples 1 to 4 and Example 1 is that the composition and content of the electrolyte additives in the electrolytes are different, see Table 1 for details, and the other steps are the same as in Example 1 to prepare lithium-ion batteries.

[0122] Table 1

[0123]

[0124]

[0125] Performance Testing

[0126] The performance tests of the lithium ion batteries prepared in Examples 1 to 23 and Comparative Examples 1 to 3 were respectively carried out, as follows:

[0127] 1. Battery DC internal resistance test

[0128] The lithium-ion battery was discharged at room temperature at a constant current of 0.33C (0.6A) to 2.0V, and charged at a constant current of 0.33C to 50% SOC (charging capacity 0.9A). The battery was discharged at a constant current of 1.5C (2.7A) for 30s, and the voltage before and after discharge was recorded. The discharge DCIR (mΩ) was calculated as (voltage before discharge - voltage after discharge) / discharge current × 1000.

[0129] 2. Battery high temperature cycle performance test

[0130] The lithium-ion battery was charged at a constant current of 1C rate (about 1.8A) to 3.8V at 60°C, and then discharged at a constant current of 1.8A to 2.0V, and the initial charging capacity and discharge capacity were recorded; after 500 cycles of charge and discharge, the discharge capacity of the 500th cycle was recorded, and the capacity retention rate after cycle was calculated (%) = (discharge capacity after 500 cycles / initial discharge capacity) × 100%.

[0131] 3. Fast charging capability test

[0132] The battery charging and discharging process is a typical diffusion mass transfer process. After lithium ions are released from the positive electrode, they need to undergo liquid phase mass transfer in the electrolyte. The solvated lithium ions diffuse to the negative electrode and then desolvate. Then the lithium ions are transported in the SEI membrane and enter the graphite layer to be reduced to lithium. When the current increases, when the lithium ions cannot quickly complete the lithium insertion and diffusion, the lithium ions will be reduced outside the graphite layer and then lithium precipitation will occur. After lithium precipitation, there will be obvious thickness changes and voltage mutations. Based on this principle, in-situ testing is used to test the fast charging and lithium precipitation boundary of the battery. The above-mentioned battery is charged and tested at a high rate current at 25°C. The distribution curve of voltage and SOC can be used to judge the fast charging capability of the battery. Figure 1 The voltage-SOC distribution curve of a lithium-ion battery at 2.5C is shown, and the SOC at the inflection point (pointed by the arrow) is the lithium deposition boundary of the battery at the corresponding current.

[0133] The results are shown in Table 2 below. The high temperature cycle and fast charging comprehensive performance of the batteries of Examples 1 to 23 are better than those of Comparative Examples 1 to 3 as a whole.

[0134] It can be seen from Examples 1 to 5 and Comparative Example 3 that the use of the first additive represented by formula (1) can reduce internal resistance while improving high temperature cycle performance and fast charging performance, among which BHT has a better effect.

[0135] It can be seen from Examples 6, 7, 17 and Comparative Example 2 that although the addition of the second additive will increase the internal resistance and reduce the fast charging performance to a certain extent, the high temperature cycle performance is significantly improved, among which MMDS has a better effect.

[0136] It can be seen from Example 1, Examples 8 to 12, and Comparative Example 1 that an appropriate amount of the first additive can further improve the high temperature cycle performance and fast charging performance of the battery. A higher amount will cause the internal resistance of the battery to be higher, and will also reduce the high temperature cycle performance and fast charging performance to a certain extent. Among them, Examples 9 and 10 have better overall performance.

[0137] It can be seen from Example 1 and Examples 13 to 15 that an appropriate amount of the second additive can further improve the high temperature cycle performance of the battery. A higher amount will cause the internal resistance of the battery to be higher and will also reduce the high temperature cycle performance and fast charging performance to a certain extent.

[0138] It can be seen from Example 1 and Examples 16 to 19 that although an appropriate amount of the third additive will slightly increase the internal resistance, its high temperature cycle performance is improved. A higher amount will cause the internal resistance of the battery to be higher, and will also reduce the high temperature cycle performance and fast charging performance to a certain extent.

[0139] It can be seen from Examples 1, 20 and 21 that the first additive, the second additive and the third additive should be used in a suitable ratio, which can further improve the high temperature cycle performance and the fast charging performance.

[0140] It can be seen from Examples 10, 15 and 22 that, compared with Example 10, Example 22 increases the amount of MMDS used, and the internal resistance of the battery increases by 5.2Ω. Example 15 simultaneously increases the amount of BHT and MMDS added, and the internal resistance of the battery increases by 5.4Ω, which indicates that the first additive and the second additive have a synergistic effect, and adding both at the same time does not significantly increase the resistance.

[0141] It can be seen from Examples 10, 18 and 23 that, compared with Example 10, Example 23 increases the amount of VC, and the internal resistance of the battery increases by 4.6Ω. Example 18 simultaneously increases the amount of BHT and VC added, and the internal resistance of the battery increases by 4Ω, which indicates that the first additive and the third additive have a synergistic effect, and adding them simultaneously will cause a slight decrease in resistance.

[0142] In summary, the battery of the present application as a whole has low resistance and good high temperature cycle performance and fast charging performance.

[0143] Table 2

[0144]

[0145]

[0146] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. An electrolyte additive, characterized in that: including a first additive and a second additive; The first additive has a structure shown in formula (I); R1, R2, R3, R4 and R5 are each independently selected from hydrogen, hydroxyl, C1-C 10 Alkyl or C1~C 10 Alkoxyl groups; The second additive includes a compound having a ring structure, and the ring structure contains a sulfur atom.

2. The electrolyte additive according to claim 1, characterized in that: The R1, R2, R3, R4 and R5 are each independently selected from hydrogen, hydroxyl, tert-butyl, -(CH2) m CH3 or -O(CH2) n CH3; m is an integer selected from 0 to 3; n is an integer selected from 0-3.

3. The electrolyte additive according to claim 1 or 2, characterized in that: At least one of R1, R2 and R5 is selected from tert-butyl.

4. The electrolyte additive according to claim 1 or 2, characterized in that: The R1, R2, R3, R4 and R5 do not contain tert-butyl groups and the formula (I) is a symmetrical conjugated structure.

5. The electrolyte additive according to any one of claims 1 to 4, characterized in that: Said R1 is selected from hydrogen, tert-butyl, methyl or ethyl; Said R2 is selected from hydrogen, hydroxyl, tert-butyl, methyl or ethyl; Said R3 and R4 are each independently selected from hydrogen, hydroxyl, methyl or ethyl; The R5 is selected from methyl, ethyl, hydroxy, methoxy, ethoxy or tert-butyl.

6. The electrolyte additive according to any one of claims 1 to 5, characterized in that: The first additive includes At least one of .

7. The electrolyte additive according to any one of claims 1 to 6, characterized in that: The cyclic structure also contains oxygen atoms; optionally, the compound having a cyclic structure includes at least one of methylene methanedisulfonate, propylene sulfite and vinyl sulfite.

8. The electrolyte additive according to any one of claims 1 to 7, characterized in that: The mass ratio of the first additive to the second additive is 1:(0.01-100), preferably 1:(1-20).

9. The electrolyte additive according to any one of claims 1 to 8, characterized in that: Further including: a third additive, the third additive comprising vinylene carbonate; Optionally, the mass ratio of the first additive to the third additive is (0.002-15):1, preferably (0.01-0.2):

1.

10. An electrolyte, characterized in that: The electrolyte additive comprises the electrolyte additive according to any one of claims 1 to 9.

11. The electrolyte according to claim 10, characterized in that Based on the total mass of the electrolyte, the mass proportion of the first additive is 0.01% to 3%, preferably 0.05% to 1%; Optionally, based on the total mass of the electrolyte, the mass proportion of the second additive is 0.1% to 5%, preferably 0.5% to 1.5%; Optionally, based on the total mass of the electrolyte, the mass proportion of the third additive is 0.1% to 10%, preferably 4% to 6%.

12. A battery, characterized in that: Comprising the electrolyte according to claim 10 or 11.

13. An electrical equipment, characterized in that: Comprising the battery as claimed in claim 12.

Citation Information

Patent Citations

  • A non-aqueous electrolyte for lithium secondary batteries

    CN102263292A

  • Non-aqueous electrolyte and lithium ion battery

    CN103887557A

  • Lithium ion battery electrolyte

    CN110459804A

  • Electrolyte and lithium ion battery containing same

    CN113764732A

  • Electrolyte and lithium ion battery containing same

    CN115036575A